(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
The study found that the differences in the yield of winter wheat varieties caused by weather conditions are much greater than by agrotechnical factors (fertilizer rates, timing and methods of sowing, variety, etc.). At the same time, weather conditions are understood as air temperature and humidity, photosynthetic active radiation and carbon dioxide concentration.